Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.4254/wjh.v7.i20.2264
|View full text |Cite
|
Sign up to set email alerts
|

Markers of bacterial translocation in end-stage liver disease

Abstract: Bacterial translocation (BT) refers to the passage of viable bacteria or bacterial products from the intestinal lumen, through the intestinal epithelium, into the systemic circulation and extraintestinal locations. The three principal mechanisms that are thought to be involved in BT include bacterial overgrowth, disruption of the gut mucosal barrier and an impaired host defence.BT is commonly observed in liver cirrhosis and has been shown to play an important role in the pathogenesis of the complications of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 96 publications
0
39
0
3
Order By: Relevance
“…Bacterial endotoxin (lipopolysaccharide [LPS]) induces high levels of proinflammatory cytokines and the release of nitric oxide, resulting in superimposed endothelial activation, splanchnic vasodilatation, thus worsening portal hypertension (PH), even in the absence of obvious infection and perpetuating BT. Several studies have evaluated whether markers of BT could identify cirrhotic patients with detrimental events and poor prognosis, but no marker has yet emerged as an ideal surrogate of BT . LPS is the culprit component of the outer surface of Gram‐negative bacteria and has thus been considered as a marker of endotoxaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial endotoxin (lipopolysaccharide [LPS]) induces high levels of proinflammatory cytokines and the release of nitric oxide, resulting in superimposed endothelial activation, splanchnic vasodilatation, thus worsening portal hypertension (PH), even in the absence of obvious infection and perpetuating BT. Several studies have evaluated whether markers of BT could identify cirrhotic patients with detrimental events and poor prognosis, but no marker has yet emerged as an ideal surrogate of BT . LPS is the culprit component of the outer surface of Gram‐negative bacteria and has thus been considered as a marker of endotoxaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Serum soluble CD14 (sCD14) is cleaved and released from membrane‐bound CD14 on peripheral blood mononuclear cells by inflammatory responses of lipopolysaccharides, with serum levels of sCD14 increasing as chronic liver disease progress . Furthermore, higher sCD14 is associated with bacterial translocation (BT) . Moreover, BT in patients with decompensated LC promotes portal hypertension and induces variceal bleeding, hepatorenal syndrome, and hepatic encephalopathy …”
Section: Introductionmentioning
confidence: 99%
“…Much evidence has suggested that elevated plasmatic levels of soluble CD14 (sCD14) are indicative of bacterial translocation . Recent studies have demonstrated a relationship between sCD14 and hepatic disease outcomes in chronically HCV‐infected individuals .…”
Section: Resultsmentioning
confidence: 99%